Anonymity of transcendental subjectivity and the idea of philosophy as a strict science - Łaciak, Piotr (Folia Philosophica, 2012)
In the paper I present the Husserl’s idea of philosophy as a strict science (Philosophie als strenge Wissenschaft) which he understood as universal and ultimately justified knowledge, free from any prejudices (Vorurteile) coming from naturalistic attitude. The prejudice of such an attitude is a thesis of the existence of the world (Thesis vom Sein der Welt). By complying with this thesis unreflectively, one becomes immersed in the world, which means that in the natural attitude the transcendental character of subjectivity remains unconscious and anonymous. This anonymity might be razed by transcendental reduction (transzendentale Reduktion), which aims at getting the transcendental ego rid of self-forgetting (Selbstvergessenheit). The subjectivity revealed this way is still, in its deepest aspects, anonymous as ultimately functioning ego (das letztfungierende Ich), for being an epistemological absolute, it is a source of reflection and through reflection it cannot become acknowledged. I discuss some difficulties related to the second type of anonymity in relation to Husserl’s demand of phenomenology realising the idea of philosophy as strict a science.